(untitled) (Dermatology Reports, 2023)
Bleomycin, an antineoplastic antibiotic that inhibits DNA synthesis, is used to treat various malignant tumors such as Hodgkin’s lymphoma, squamous cell carcinoma, and germ cell tumors. Flagellate erythema is a rare rash with a linear pattern that has been observed in association with bleomycin treatment. Herein, we present a 43-year-old patient with metastatic testicular cell neoplasms who developed a whiplash rash during treatment with a chemotherapy regimen that included bleomycin. A typical case of bleomycin-related flagellate dermatitis has been diagnosed and the main features of this characteristic adverse drug event are briefly discussed.